2010
DOI: 10.1523/jneurosci.0588-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Frontoparietal Networks Set the Stage for Later Perceptual Identification Priming and Episodic Recognition Memory

Abstract: Recent imaging evidence suggests that a network of brain regions including the medial temporal lobe, ventrolateral prefrontal cortex, and dorsal posterior parietal cortex supports the successful encoding of long-term memories. Other areas, like the ventral posterior parietal and dorsolateral prefrontal cortices, have been associated with encoding failure rather than success. In line with the transfer-appropriate processing view, we hypothesized that distinct neural networks predict successful encoding dependin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 53 publications
(97 reference statements)
3
20
0
Order By: Relevance
“…Schott et al (2002) proposed that modulations of this negative-going waveform associated with later priming may be related to the efficiency with which words are perceptually and lexically processed. Wimber et al (2010) suggested that the negative DM effect might reflect stimulus-driven attentional orienting at encoding, which was unfavorable for later recognition memory, but facilitated later perceptual identification. The present findings support these accounts.…”
Section: 2mentioning
confidence: 99%
See 4 more Smart Citations
“…Schott et al (2002) proposed that modulations of this negative-going waveform associated with later priming may be related to the efficiency with which words are perceptually and lexically processed. Wimber et al (2010) suggested that the negative DM effect might reflect stimulus-driven attentional orienting at encoding, which was unfavorable for later recognition memory, but facilitated later perceptual identification. The present findings support these accounts.…”
Section: 2mentioning
confidence: 99%
“…In contrast, the priming-without-recognition DM included reduced activity in bilateral occipital and prefrontal cortex and left fusiform gyrus. Wimber et al (2010) adopted a combined incidental perceptual identification and intentional recognition memory test to sort study trials into later remembered items (words that were later identified and correctly recognized as studied), later-primed items (words that were later identified but not recognized as studied), and later-nonidentified items (words that later elicited no identification response, or were incorrectly identified as other words). They found two distinct frontoparietal cortical networks that predicted later incidental perceptual identification priming and later intentional recognition memory.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations